2021
DOI: 10.3390/ijerph19010029
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Method for Ease Determination of Sodium Diclofenac Trace Levels in Water Using Graphene—Multi-Walled Carbon Nanotubes Paste Electrode

Abstract: Sodium diclofenac (DCF) presence reported in water use cycle at various concentrations including trace levels necessitates continuous development of advanced analytical method for its determination. In this work, ease electrochemical methods for DCF determination based on voltammetric and amperometric techniques were proposed using a simple combination of graphene with multi-walled carbon nanotubes as paste electrode. Integration of the graphene with multi-walled carbon nanotubes enlarged the electroactive sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…At a scan frequency of 100 mV s −1 , the optimal variables were 200 mV of MA and 50 mV of SP. Figure 5 analytical curves [90]. This DCF content region, which was increased to 1 mg l −1 DCF, showed a straight dependence having a strong correlation coefficient.…”
Section: Carbon Nanotube (Cnt)mentioning
confidence: 79%
See 1 more Smart Citation
“…At a scan frequency of 100 mV s −1 , the optimal variables were 200 mV of MA and 50 mV of SP. Figure 5 analytical curves [90]. This DCF content region, which was increased to 1 mg l −1 DCF, showed a straight dependence having a strong correlation coefficient.…”
Section: Carbon Nanotube (Cnt)mentioning
confidence: 79%
“…It may also modify the aspect proportion at the nanoscale scale to improve the specific surface region, which has drawn interest and has several potential applications in electrochemical sensing. In an experiment, utilizing a simplistic blend of MWCNT and graphene as the paste electrode for an electrochemical sensor, Motoc et al [90] suggested basic electrochemical techniques for sodium diclofenac (DCF) measurement centered on amperometric and voltammetric methodologies. They discovered that the preconcentration stage used before multiple-pulsed amperometry (MPA) and DPV permitted the augmentation of the electroanalytical effectiveness of the DCF electrochemical detection systems affirmed by evaluating in tap water.…”
Section: Carbon Nanotube (Cnt)mentioning
confidence: 99%
“…Before UA electrooxidation, the electroactive surface areas were determined for each composition using a classical ferri/ferrocyanide system, described in detail in our previous publications [ 35 , 36 , 37 ]. A higher content of carbon nanotubes and lower content of Zn_MM required a higher content of paraffinic oil to ensure a mechanical stability of the electrode and better distribution of CNT.…”
Section: Resultsmentioning
confidence: 99%
“…The reference electrode may also serve as auxiliary electrode for low current values in the range of 10 −9 to 10 −6 A. The resulting current is directly correlated to the bulk concentration or the production/consumption rate of the electroactive species in the adjacent biocatalytic layer [72]. (d) Conductometry-is based on the usage of interdigitated microelectrodes, by ion conductometric or impedimetric devices.…”
Section: Electrochemical Transduction Methodsmentioning
confidence: 99%